An unusual cause of ileal volvulus, a giant mesenteric cystic lymphangioma - Nouha Boubekri, MD; Amal Akammar, MD; Hajar Ouazzani, MD; Ismail Chaouche, MD; Nizar El Bouardi, MD; Meriem Haloua; Badreddine Alami, MD; Moulay Youssef Lamrani Alaoui, MD; Mustapha Maaroufi, MD; Meryem Boubbou, MD (Radiology Case Reports)
Volvulus of the midgut involves twisting of the small bowel around its mesenteric axis. It is frequently associated with malrotation in children, it can also be attributed to other causes such as tumors. Mesenteric lymphangiomas account for only 5% of all lymphangiomas, and small bowel lymphangiomas represent less than 1% of all cases. The combination of small bowel volvulus secondary to a lymphangioma is exceedingly rare, with only a handful of cases reported in the literature. Our case was a 3 years old patient, admitted for acute abdominal pain. The abdominal radiological explorations found a large lobulated cystic mass occupying the entire pelvic cavity and surrounding digestive structures, suggestive of a mesenteric cystic lymphangioma, with a volvulus of the mesenteric pedicle creating a whirlpool sign. The patient underwent surgery and recovered well.